CMB constraints on cosmic strings and superstrings - Charnock, Tom; Avgoustidis, Anastasios; Copeland, Edmund J.; Moss, Adam (American Physical Society, 2016)
We present the first complete MCMC analysis of cosmological models with evolving cosmic (super)string networks, using the Unconnected Segment Model in the unequal-time correlator formalism. For ordinary cosmic string networks, we derive joint constraints on ΛCDM and string network parameters, namely the string tension Gμ, the loop-chopping efficiency cr and the string wiggliness α. For cosmic superstrings, we obtain joint constraints on the fundamental string tension GμF, the string coupling gs, the self-interaction coefficient cs, and the volume of compact extra dimensions w. This constitutes the most comprehensive CMB analysis of ΛCDM cosmology + strings to date. For ordinary cosmic string networks our updated constraint on the string tension, obtained using Planck2015 temperature and polarisation data, is Gμ < 1.1 × 10^(−7) in relativistic units, while for cosmic superstrings our constraint on the fundamental string tension after marginalising over gs, cs and w is GμF < 2.8 × 10^(−8).